A case study systems approach to non-formal education in an agri-business setting - Diaz, Aurea T. (Aurea Tayao) 1921-
The study dealth with development of a new type of farm labor by providing input trends, human skills, human resources, physical resources and outputs (knowledge, skills, habits, attitudes, etc.) to nine trainees and an equal number of demontrators-trainors from BarrioSta. Arcadia, Caloocan City. A curriculum geared to national development goals was drafted on the different aspects of farming. Results revealed that young unskilled rice farm workers with only an elementary education can be trained to become skilled workers or farmers. The farm training program developed in them certain positive values which increase their community life participation through better farm technology.